PENERAPAN MODEL PEMBELAJARAN TEAMS GAME TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS VI SEMESTER I SD N0.6 PANJI KECAMATAN SUKASADA - Ni Luh Putu Anggreni; I Gede Margunayasa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2016)
The aim of this research is to know the improvement the result of learning social studies after the implementation of Temas Game Tournament (TGT) model on the first semester of sixth grade students of SD No 6 Panji in academic year 2014/2015. This research was an action research. This research was done at SD No 6 Panji on sixth grade students in academic year 2014/2015 which was consisted of 14 students, 8 males and 6 females. The method of data collection in this research was test method. The method of data analysis was descriptive quantitative analysis method. In the cyclic process, the action was done successfully if the percentage of the learning achievement reached ≥ 80 % and if all students got score ≥ 56. The result of the research showed that there was an improvement of the average score of social studies students’ achievement on cycle1 was 60,71 with the classical passing standard of learning 71,43%. There were 10 students passed and 4 students were not passed. There was an improvement on cycle 2 on the average score 80,71 with the classical passing standard of learning 100%. So forth, the implementation of teaching and learning by using TGT model could improve the result of the students’ outcome for sixth grade studentson the first semester of SD No 6 Panji in academic year 2014/2015